Customer Gap Pelayanan BPJSKesehatan Center - Indira Probo Handini; Djazuly Chalidyanto (Universitas Airlangga, 2015)
ABSTRACTAfter almost 2 years implementation of National Health Insurance (JKN) held by Health Social Insurance Organizing Board (BPJS Kesehatan), many evaluation needs to be done. One of them is BPJS Kesehatan Center located in hospital that provide direct service for patients who referred by the First Level Health Care (FKTP). This studyaim to analyzecustomer gap betweenexpected serviceand perceived service patientsinBPJS Kesehatan CenterRSALdr. RamelanSurabaya. This is an observasional study and cross sectional analytic design. Sample were in equal to 95 people and collected by systematic random sampling. Samples were outpatients who ever used BPJS Kesehatan Center service in RSAL dr. Ramelan Surabaya. Data were collected by questionnaires and calculated by Customer Gap to identify the differences between expected service and perceived service. Data were processed by Wilcoxon Sign Rank Test (α = 0,05). The results showedmost respondentshadvery high expectationsandreceived quite good services. Wilcoxon SignRankTestshowedthere is a differencebetweenthe expected service and perceived service (p = 0,000). This studyconcluded that customer gap in all aspects of BPJS Kesehatan Center service, such as competency, responsiveness, assurance, empathy, communication, caring, dan physical environment. Negative result indicates that expectedservice (ES) is greater than theperceived service(PS). Respondentsare not satisfiedwith the overallperceived serviceatBPJS Kesehatan Center.Keywords : BPJS Kesehatan Center, customer gap, expected service, perceived service